Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4149/av_2018_109
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin, a flavonoid isolated from Scutellaria baicalensis, has anti-viral activities against influenza infection via modulation of AMPK pathways

Abstract: Wogonin, a flavonoid isolated from Scutellaria baicalensis, has attracted increasing scientific attention in recent years because of its potent anti-tumor activity. Its role during viral infection has largely been unexplored. Wogonin treatment effectively suppressed both influenza A and B virus replication in Madin-Darby Canine Kidney (MDCK) cells and human lung epithelial (A549) cells. In contrast, wogonin treatment following influenza A virus infection led to up-regulation of interferon (IFN)-induced antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Additionally, kaempferol regulates the transcription factor and protein kinase to suppress on virus-induced inflammation [50]. One previous study suggests that kaempferol may be regarded as an effective drug for the potential treatment of influenza virus-induced acute lung injury [51]. Wogonin was attested to suppress the replication of multiple viruses, such as varicella-zoster virus and influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, kaempferol regulates the transcription factor and protein kinase to suppress on virus-induced inflammation [50]. One previous study suggests that kaempferol may be regarded as an effective drug for the potential treatment of influenza virus-induced acute lung injury [51]. Wogonin was attested to suppress the replication of multiple viruses, such as varicella-zoster virus and influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…Wogonin (Fig. 2) is a plant flavonoid extracted from roots of Scutellaria baicalensis, Scutellaria amoena and Scutellaria rivularis, and stem of Anodendron affine Druce, and has many pharmacological effects including anti-viral, anti-oxidative, anti-inflammatory, anti-cancer and neuroprotective activities [702][703][704][705]. It has various anti-cancer effects in many cancers, including lung, breast, head and neck, gastric and colorectal cancers, glioma, leukemia, lymphoma, and osteosarcoma, through the induction of apoptosis and cell cycle arrest, and inhibition of cell growth, migration, invasion, and angiogenesis [706][707][708][709][710][711][712][713][714][715][716].…”
Section: Wogoninmentioning
confidence: 99%
“…Wogonin, a naturally occurring flavonoid, has been shown to multi-activity, such as anti-inflammatory, anti-fibrosis, anti-cancer and chondroprotective properties [37]. Study showed that wogonin had an anti-infulenza activity by modulation of AMPK pathway [38]. Licochalcone a, a flavonoid extracted from licorice toot, was known for its anti-inflammatory, anti-cancer, anti-oxidative and anti-bacterial bioactivity [39].…”
Section: Discussionmentioning
confidence: 99%